The Effect of Teacher Welfare and Teacher Work Motivation on the Professionalism of High School Teachers - Ikram Arrazy; Nila Kesumawati; Djunaidi Djunaidi (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aims to determine and analyze the influence of teacher welfare and teacher work motivation on the professionalism of high school teachers in Sungai Lilin District. A quantitative approach with a survey method was employed. The population comprised public and private high school teachers in the district, with a sample of 108 teachers. Data were collected through questionnaires and analyzed using inferential statistics, including prerequisite tests, simple and multiple linear regression, t-tests, F-tests, and coefficient of determination. Findings reveal that: (1) teacher welfare significantly influences teacher professionalism (t = 8.544; p < 0.05); (2) teacher work motivation significantly influences teacher professionalism (t = 10.263; p < 0.05); and (3) simultaneously, both variables exert a positive and significant effect (F = 82.785; p < 0.05). The coefficient of determination (R² = 0.612) indicates that teacher welfare and work motivation jointly explain 61.2% of the variance in teacher professionalism, with the remaining 38.8% attributed to other factors. This study provides empirical evidence from a district-level context in Sungai Lilin, demonstrating the combined predictive power of welfare and motivation on teacher professionalism in an under-researched setting. Findings recommend that school principals, government, and stakeholders continuously prioritize teacher welfare, create supportive work environments, and provide awards and coaching to sustain motivation. This research contributes actionable insights affirming that teacher professionalism is substantially enhanced through integrated welfare improvement and motivation strengthening, offering a foundational reference for policy formulation in secondary education.